1986
DOI: 10.1055/s-2008-1048786
|View full text |Cite
|
Sign up to set email alerts
|

Erfahrungen mit der präoperativen und palliativen perkutanen transhepatischen Cholangiodrainage (PTCD)

Abstract: In obstructive jaundice PTCD plays an important role as a preoperative or a palliative therapeutic method inspite of the availability of biliary endoprostheses. This study was carried out to assess complications following PTCD, the effect on liver function (serum parameters) and the relationship between duration of preoperative drainage and postoperative complication rate. The results demonstrate that 11-hole pigtail-catheters are useful for intrahepatic location and 32-hole ringcatheters for extrahepatic loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

1991
1991
2008
2008

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
1
0
1
Order By: Relevance
“…Generally, bacteriobilia does not necessarily lead to clinically significant infection (17,19,20), but it may become relevant in cases of impaired biliary flow, with increasing pressure and potential transfer of bacteria into the bloodstream (6,21). Other studies have reported variable results, with cholangitis rates ranging from 6%-7% (22,23) to 14% (24), with simple fever occurring in 14%-46% (22,24). Nevertheless, general antibiotic coverage for PTBD, especially during the initial phase of placement, is therefore not uniformly recommended, because of problems with bacterial resistance.…”
Section: Discussionmentioning
confidence: 96%
“…Generally, bacteriobilia does not necessarily lead to clinically significant infection (17,19,20), but it may become relevant in cases of impaired biliary flow, with increasing pressure and potential transfer of bacteria into the bloodstream (6,21). Other studies have reported variable results, with cholangitis rates ranging from 6%-7% (22,23) to 14% (24), with simple fever occurring in 14%-46% (22,24). Nevertheless, general antibiotic coverage for PTBD, especially during the initial phase of placement, is therefore not uniformly recommended, because of problems with bacterial resistance.…”
Section: Discussionmentioning
confidence: 96%
“…Die Komplikationsrate von etwa 40% infolge Cholangiitis oder Prothesenverschluß war bei beiden Patientengruppen gleich (15,20). Die genannten Zahlen stimmen mit den Angaben in der Literatur zur palliativen Gallenwegsdrainage überein (1,17,33…”
Section: Was Ist Endoskopisch Möglich?unclassified